AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA PADA BADAN USAHA MILIK DESA SEJAHTERA MANDIRI - Aulia Nurushifa, - (2019)
This study describes how the accountability of village fund arrangements at BUMDes Sejahtera Mandiri in Karya Utama Village, Cikedal Subdistrict, Pandeglang District, starting from the budget planning process, BUMDes capital, implementation of BUMDes activity budget, and accountability of BUMDes capital participation funds. This study uses descriptive qualitative with the interpretive paradigm and through ethnometodology studies. The results of this study discuss Financial Management carried out by the village of Karya Utama as a capital fund provider for BUMD starting from budget planning, implementation, to accountability that has been carried out accountable where it is in accordance with applicable laws and regulations. In contrast to the financial management carried out by the Prosperous Mandir BUMDes, there are still some who have not been approved accountable, in the process of implementing BUMDes Sejahtera Mandiri still making simple financial reports that are in accordance with the existing standards of financial statements. For suggestions and recommendations that can be given, namely by applying independent controls on the making of financial statements for BUMDes Sejahtera Mandiri.